Space-Charge Limitation of a Femtosecond Photoinjector - Hiroko Yamamoto; Hiroaki Hamabe; Shintaro Sone; Soichiro Yamaguchi; Makoto R. Asakawa (International Journal of Optics)
Experimental investigation of a compact 40-kV diode-type photoelectric DC gun driven by 100 fs laser pulses revealed that the space-charge-limited current density could exceed 30 kA/cm2 and that the density increased linearly with the accelerating voltage. We explained these important properties by the balance between the cathode surface field and the field produced by sheet-like electron bunches near the cathode surface. Our simple physical model agreed well with the experimental results.